2007
DOI: 10.1111/j.1348-0421.2007.tb03965.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1*0410‐Restricted Recognition of XAGE‐1b37‐48 Peptide by CD4 T Cells

Abstract: XAGE‐1b belongs to cancer/testis (CT) antigens, and has been shown to be expressed frequently in lung cancers and to elicit an antibody response in patients with XAGE‐1b‐expressing tumors. In this study, we investigated an XAGE‐1b peptide recognized by CD4 T cells. CD4 T cells were purified from PBMC of a healthy donor and stimulated with pooled 25‐mer peptides overlapped with 15 amino acids spanning the entire XAGE‐1b protein. The generation of XAGE‐1b‐specific CD4 T cells was shown by IFN7 secretion assay. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…We demonstrated that, for all fine specificities, peptide recognition was restricted by HLA-DR. By assessing antigen presentation using APC that share single HLA-DR alleles with those of the patient, we determined that antigen recognition by the clones was restricted by the DRB1*13 allele. It is noteworthy that, whereas other XAGE-1b MHC class II epitopes restricted by other alleles have been reported [ 19 , 23 , 24 ], DRB1*13 restricted epitope described here has not been previously reported.…”
Section: Discussioncontrasting
confidence: 50%
“…We demonstrated that, for all fine specificities, peptide recognition was restricted by HLA-DR. By assessing antigen presentation using APC that share single HLA-DR alleles with those of the patient, we determined that antigen recognition by the clones was restricted by the DRB1*13 allele. It is noteworthy that, whereas other XAGE-1b MHC class II epitopes restricted by other alleles have been reported [ 19 , 23 , 24 ], DRB1*13 restricted epitope described here has not been previously reported.…”
Section: Discussioncontrasting
confidence: 50%
“…In this study, we determined the DRB1*04:05‐restricted XAGE‐1b (GAGED2a) 18–31 peptide (14‐mer) as a CD4 T‐cell epitope, and the A*02:06‐restricted XAGE‐1b (GAGED2a) 21–29 peptide (9‐mer) as a CD8 T‐cell epitope. We previously determined two XAGE‐1b (GAGED2a) CD4 epitope peptides restricted to DRB1*04:1032 and DRB1*09:01 33. Moreover, we are currently determining other MHC I binding peptide epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibody responses to recombinant L552S protein, an alternatively spliced isoform of XAGE-1, were observed in the pleural effusion fluids of lung cancer patients (25). The XAGE-1b protein can be processed, is present in the HLA-I molecule and stimulates the autologous CD4 + T-lymphocyte response (26,27). Patients with lung adenocarcinoma expressing both XAGE-1b and HLA class I antigens were associated with prolonged survival time (28).…”
Section: Primermentioning
confidence: 99%